General factors affecting drug metabolism: effect of physiological factors and disease 1 - Morgan, Edward T. (Henry Stewart Talks, 2007)
Effect of physiological and pathophysiological conditions on drug-metabolizing enzymes (DMEs), Role of growth hormones and transcription factors in sex-dependent expression, Drug clearance and age, Developmental regulation, Impact of infection and inflammatory disease on DME expression, Clinical consequences
Updated at 2017/07/31